Dissecting the mechanisms of environment sensitivity of smart probes for quantitative assessment of membrane properties - Ragaller, Franziska; Andronico, Luca; Sykora, Jan; Kulig, Waldemar; Rog, Tomasz; Urem, Yagmur Balim; Abhinav; Danylchuk, Dmytro I; Hof, Martin; Klymchenko, Andrey; Amaro, Mariana; Vattulainen, Ilpo; et al. (Open biology, 2022)
The plasma membrane, as a highly complex cell organelle, serves as a crucial platform for a multitude of cellular processes. Its collective biophysical properties are largely determined by the structural diversity of the different lipid species it accommodates. Therefore, a detailed investigation of biophysical properties of the plasma membrane is of utmost importance for a comprehensive understanding of biological processes occurring therein. During the past two decades, several environment-sensitive probes have been developed and become popular tools to investigate membrane properties. Although these probes are assumed to report on membrane order in similar ways, their individual mechanisms remain to be elucidated. In this study, using model membrane systems, we characterized the probes Pro12A, NR12S and NR12A in depth and examined their sensitivity to parameters with potential biological implications, such as the degree of lipid saturation, double bond position and configuration (cis versus trans), phospholipid headgroup and cholesterol content. Applying spectral imaging together with atomistic molecular dynamics simulations and time-dependent fluorescent shift analyses, we unravelled individual sensitivities of these probes to different biophysical properties, their distinct localizations and specific relaxation processes in membranes. Overall, Pro12A, NR12S and NR12A serve together as a toolbox with a wide range of applications allowing to select the most appropriate probe for each specific research question.
Keywords: time-resolved emission shift; Cholesterol; Molecular Dynamics Simulation; cholesterol; Fluorescent Dyes; lipid saturation; simulace molekulární dynamiky; MD simulation; buněčná membrána; model membranes; spectral imaging; fluorescenční barviva; Cell Membrane; environment-sensitive probes